Eleocharis obtusetrigona (Cyperaceae) new to North and Central America - González-Elizondo, M. Socorro; González-Elizondo, Martha; Smith, S. Galen (Instituto de Ecología, A.C., 2002)
Eleocharis obtusetrigona (Lindl. & Nees) Steud., previously known only from South America, is recorded here for southeastern United States, Mexico and Central America. A description of the species is presented, as well as a key to separate E. obtusetrigona from other robust species of subgenus Limnochloa with which it has been confused.